Salicylic acid metabolism and signalling coordinate senescence initiation in aspen in nature - Lihavainen, Jenna; Šimura, Jan; Bag, Pushan; Fataftah, Nazeer; Robinson, Kathryn Megan; Delhomme, Nicolas; Novák, Ondřej; Ljung, Karin; Jansson, Stefan (Nature communications, 2023)
Deciduous trees exhibit a spectacular phenomenon of autumn senescence driven by the seasonality of their growth environment, yet there is no consensus which external or internal cues trigger it. Senescence starts at different times in European aspen (Populus tremula L.) genotypes grown in same location. By integrating omics studies, we demonstrate that aspen genotypes utilize similar transcriptional cascades and metabolic cues to initiate senescence, but at different times during autumn. The timing of autumn senescence initiation appeared to be controlled by two consecutive "switches"; 1) first the environmental variation induced the rewiring of the transcriptional network, stress signalling pathways and metabolic perturbations and 2) the start of senescence process was defined by the ability of the genotype to activate and sustain stress tolerance mechanisms mediated by salicylic acid. We propose that salicylic acid represses the onset of leaf senescence in stressful natural conditions, rather than promoting it as often observed in annual plants.
Keywords: signální transdukce; genotyp; roční období; Seasons; Genotype; Signal Transduction